Hydrodynamic behavior of the oscillating water column resonant chamber (2024)
ABSTRACT: Wave energy converters (WEC) may be a promising option for extracting the energy available in the sea and ocean in a clean way. The oscillating water column (OWC) is one of the most well-known and applicable WEC systems. In this work, computational fluid dynamics (CFD) was employed to simulate an OWC at the shore numerically adapted to the Pacific Ocean conditions. For this purpose, ANSYS-Fluent software was used, and Reynolds-Averaged Navier Stokes (RANS) equations were solved through the program in two dimensions. The Volume of Fluid (VOF) scheme and the laminar viscosity model were used for the description of the water-air interface and the fluid modeling, respectively. The regular waves were generated using Stokes second-order nonlinear theory by directly fitting as input the boundary condition as an open channel wave and the volume fraction parameters through implicit formulation. The variation of the free water surface elevation and the pressure drop inside the resonance chamber were investigated; the results showed that for the studied OWC, an efficiency of 0.672 was obtained.